Nitrificação e aproveitamento de alguns adubos nitrogenados - Malavolta, E.; Coury, T.; Arzolla, J. D. P.; Haag, H. P.; Brasil Sobrinho, M. O. C. do (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1958)
The rate of nitrification of several nitrogenous fertilizers (ammonium sulfate, nitre-chalk, ureia, and cottonseed meal) was studied in three soils, namely, "terra roxa legítima", a red soil derived from basalt, "terra roxa misturada", a soil also derived from basalt but with a higher proportion of sand, and "areito Corumbataí", a sandy soil. The effects of the following treatments on nitrification were considered: addition of limestone of micronutrients (Fe, Cu, Zn, Mn, and Mo), and inoculation with a suspension of spores of Aspergillus wentii, a heterotrophic nitrifier. The results showed that: in "terra roxa legítima" limestone had no influence on the nitrification rate, whereas the micronutrients estimulated the oxidation of nitre-chalk, cottonseed meal and urea; inoculation with A. wentii helped only the nitrification of ammonium sulfate and of the cottonseed meal; the latter, in all the treatments employed gave use to a smaller amount of nitrates; in "terra roxa misturada", all the fertilizers depending upon the treatments they were subjected to, presented maximum values for nitrification; limestone estimulated the oxidation of ammonium sulfate as well as the mineralization of the cottonseed meal; the addition of micronutrients helped the nitrification of all the fertilizers, except that of urea; inoculation showed a benefical influence on the nitrification of ammonium sulfate and cottonseed meal; in "arenito de Corumbatai", the amounts of nitrates produced was roughly the same for all the fertilizers investigated; limestone estimulated the nitrification of nitro-chalk, ammonium sulfate and cottonseed meal whilst the addition of micronutrients benefited only the latter two; the inoculation with A. wentii helped the oxidation of all the fertilizers. In order to study the availability of the various fertilizers above discussed, two plant growing experiments were carried cut, one in pots, using the three soil types and another one in the field, with "terra roxa misturada". In "arenito de Corumbatai" there was no significant difference in the yield both of straw and rice grains for none of the fertilizers: Chilean nitrate of soda was used as a control; ho marked agreement could be detected between the data concerning nitrification and the yield results. In "terra roxa legítima", ammonium sulfate won the competition and there was a good parallelism between nitrification and yield. In "terra roxa misturada", there was no statistical difference among the various fertilizers; the agreement between nitrification and yields was reasonable. In the field (corn), Chilean nitrate, ammonium sulfate and nitro-chalk were clearly beter than urea and cottonseed meal which did not differ from the minus nitrogen plots.